Some aspects of scientific article in Revista Peruana de Biología - Romero, Leonardo (2015)
This paper presents some characteristics of the articles of Revista Peruana de Biologia. Aspects of the peer review process, about article type: the data paper, the problem on lack of scholarship in the submitted manuscripts, the importance of reproducibility and authorship.